The relationship between social support and depression among HIV-positive men who have sex with men in China: the chain mediating role of psychological flexibility and hope - Wang, Run; Zheng, Fang; Cao, Guiying; Goldsamt, Lloyd A.; Shen, Yan; Zhang, Ci; Yi, Mengyao; Peng, Wenwen; Li, Xianhong (Frontiers in Public Health, 2023)
HIV and mental health problems are a global syndemic. One key issue is that the significant mental health problems among people vulnerable to acquiring or living with HIV have not been fully addressed. Access to social support has been one of the biggest challenges for HIV-positive men who have sex with men. Lower social support had been related to more severe depression symptoms. However, the mechanisms underlying the association between social support and depression in HIV+MSM are unclear. Two possible mediators include hope and psychological flexibility. This study aimed to examine the relationship between social support and depression in HIV+MSM and to explore the single mediating effects of hope and psychological flexibility and the chain mediating effect of these two variables on this relationship. A convenience sample was used to recruit participants from the designated HIV/AIDS hospital in Changsha City, Human Province of China. A total of 290 HIV+MSM completed questionnaires. Our findings showed that hope mediated the relationship between social support and depression in HIV+MSM. Furthermore, the chain mediation model confirmed a direct negative association between social support and depression, but this relationship was largely mediated by the chain effects of hope and psychological flexibility. Integrating hope and psychological flexibility into interventions may provide better mental health support for HIV+MSM and improve their well-being and quality of life.